Python's Pivotal Role in AI and Data Science - Srinivas Sriram Mantrala (Malikussaleh University, Aceh, Indonesia, 2026)
Python has established itself as the dominant programming language in Artificial Intelligence (AI) and Data Science, fundamentally transforming how researchers, developers, and organizations address increasingly complex computational challenges. Its combination of simplicity, readability, flexibility, and an extensive open-source ecosystem has significantly accelerated AI research, application development, and industrial adoption across diverse sectors. This article presents a comprehensive review of Python's evolution as the primary programming language for AI and Data Science, examining the technical and organizational factors underlying its widespread acceptance. The study analyzes Python's rich ecosystem of libraries and frameworks, including NumPy, Pandas, Scikit-learn, TensorFlow, PyTorch, Keras, OpenCV, and Hugging Face Transformers, which collectively provide comprehensive support for data processing, machine learning, deep learning, computer vision, natural language processing, and predictive analytics. Furthermore, the article explores Python's advantages in rapid prototyping, cross-platform compatibility, cloud integration, reproducible research, and interoperability with high-performance computing environments. Evidence from recent academic literature and industry reports demonstrates that Python has substantially reduced development time, improved collaboration between multidisciplinary teams, and democratized access to advanced AI technologies by lowering technical barriers for students, researchers, and practitioners. The review also discusses emerging application domains in which Python continues to drive innovation, including AutoML, reinforcement learning, edge AI, generative AI, explainable AI, and AI-powered scientific computing. Despite challenges related to execution speed and memory efficiency compared with compiled languages, Python remains the preferred language due to continuous ecosystem improvements and seamless integration with optimized computing libraries. The findings confirm that Python has become the universal programming language connecting human creativity, data-driven decision-making, and intelligent machine systems, thereby reinforcing its strategic role in the future development of Artificial Intelligence and Data Science.